Teacher Strategies in Cultivating Good Character in Early Childhood - Nedya Varchati; Biqi Zain; Phaisan Toryib (HADHANATUNA: Journal of Early Childhood Education, 2025)
This research is motivated by the phenomenon that instilling morals such as honesty, helpfulness, and responsibility in children needs to be done from early childhood, as these values form the foundation of good character. Character development in education has become a significant concern because many students still show weaknesses in moral behavior. Therefore, early moral education is essential to guide children in forming positive attitudes and preparing them to interact responsibly in society. The purpose of this research is (1) to know Teacher’s Strategy in Cultivating Honest Attitude in Early Childhood at RA Darul Muttaqin Taman Harjo Semendawai Tribe III Oku Timur Palembang Sumsel. (2) to know Teacher’s Strategy in Cultivating Mutual help attitudein Early Childhood at RA Darul Muttaqin Taman Harjo Semendawai Tribe III Oku Timur Palembang Sumsel?. In this research the authors used a qualitative approach, a descriptive type of approach. In collecting data, researchers used observation, interview and documentation methods. The method of observation and researcher interviews was used to obtain data related to teacher strategies in instilling morals in early childhood. While the documentation method is used by researchers to extract data. The results showed that the strategy used in cultivating akhlakul karimah in early childhood was habituation strategy, giving understanding and motivation to children so that children get used to doing good things.